Newly developed Zinc-Tellurite glass system: An experimental investigation on impact of Ta2O5 on nuclear radiation shielding ability - Kavaz, E.; Tekin, H.O.; Kilic, G.; Susoy, G. (Journal of non-crystalline solids, 2020)
•Newly developed Zinc-Tellurite glasses have been fabricated.•Nuclear shielding characterization of fabricated glasses was studied.•The experimental results then compared with simulated MCNPX and theoretical WinXCOM data.•ZTT3 glass sample with highest Ta2O5 contribution has excellent nuclear radiation shielding ability. In this paper, the nuclear shielding properties of newly fabricated Zinc-Tellurite glasses doped with Ta2O5 with a composition (25ZnO.75TeO2)100-x.(Ta2O5)x (x=0, 1, 2, 3 mol%) were studied. Ta2O5 doped Zinc-Tellurite glasses prepared by the traditional melt quenching method. The mass attenuation coefficients were achieved for prepared glasses at 0.081-0.383 MeV photon energies employing experimental transmission measurements, which were performed with 3 Ci Ba-133 point source and Ultra Ge detector. The experimental results were compared with simulated MCNPX and theoretical WinXCOM data. Moreover, another important nuclear shielding parameters such as mass attenuation coefficient, half value layer, effective atomic number, effective electron density, equivalent atomic numbers, alpha and proton projected ranges, mass stopping power in the protection of gamma, neutron, alpha and proton radiation were calculated. In addition, buildup factors of investigated glasses were determined by using the G-P fitting method. Moreover, effective removal cross section ΣR and transition factors were determined. According to the results, the addition of Ta2O5 to the glass samples has a positive effect on the performance of nuclear shielding effects of the glass samples. It can be concluded that ZTT3 glass sample with the highest Ta2O5 contribution has excellent nuclear radiation shielding ability among the other fabricated glass samples.